Alice's adventures in wonderland - Carroll, Lewis; Parreño, Fran (Usborne London, 2013)
A superb gift edition of Lewis Carroll's complete and unabridged text. Fantastic new illustrations re-imagine the much-loved characters of Alice, the White Rabbit, the Mad Hatter, the Red Queen, the Mock Turtle and the rest. The story of Lewis Carroll and how he came to write this much-loved tale is told at the back of the book.